Uji Efek Sitotoksik Ekstrak Etanol Akar Asam Kandis (Garcinia Cowa Roxb.) pada Mencit Putih Betina dengan Metode Micronucleus Assay - Wahyuni, Fatma Sri; Siregar, Fitriyani; Dharma, Surya (Jurnal Sains dan Teknologi Farmasi, 2012)
The cytotoxic effect of ethanolic extract of Garcinia cowa Roxb. roots had been investigated on female mice using Micronucleus Assay method. Sixty mice were grouped into five: negative control, positive control, dosage I (extract 30 mg/kgBW), dosage II (extract 100 mg/kgBW), and dosage III (300 mg/kgBW) and then each group were grouped into three groups based on the duration of treatment. The group of mice were induced by cyclophosphamide 50 mg/kgBW intraperitoneally. After 30 hours, the treatment groups were administered the extract orally during 3, 7, and 15 days. After that, mice were sacrificed and the femur bone marrow was taken. Some of cytotoxic parameters were observed i.e micronuclei cells and hematocrit level. The percentage of micronuclei (MN) cells was calculated from the quantity of micronuclei cells of the slides of femur bone marrow by using microscope. Results confirmed that ethanolic extract of Garcinia cowa Roxb. roots decreased percentage of micronuclei cells not significantly (P > 0.05). The most lowering of micronuclei cells was showed by the extract in the dosage of 100 mg/KgBW for 15 days.